Electrochemical method for Ag-PEG nanoparticles synthesis - Roldan, Maria Virginia (2013)
In this work we present an electrochemical method to successfully prepare silver nanoparticles using only polyethylene glycol as stabilizer and without any other reactive. Here we study the use of the polymeric stabilizer to allow the introduction of a potential tool to reinforce the control of the size and shape of the nanoparticles throughout the synthesis process. The evolution of the reactions was followed by UV-Vis spectroscopy. The electrode processes were characterized by cyclic voltammetric measurements and the final product was studied by Atomic Force Microscopy, Transmission Electron Microscopy, and X-Ray Diffraction. The influences of the current density, polymer length, and concentration media were analyzed.